Body-Surface-Area Related Renal Volume: A Common Normal Range from Birth to Adulthood - Th. Scholbach; D. Weitzel (Scientifica)
Renal volume is an important parameter of renal development. Deviations from normal volume may indicate pathologic conditions. Thus, during childhood, the ever changing renal volumes require the continuous referral to normal volume charts in order to classify actual volumes, which is rather inconvenient. In daily practice this is frequently disregarded and kidneys are evaluated by their appearance only. Therefore, we tested the hypothesis that body surface area (BSA) and renal volume grow proportionally from birth to adulthood. We divided the renal volume of a child by its BSA to get the BSA-related renal volume (BSARV) and found no differences between left and right kidneys and a normal distribution for all kidneys regardless of the patient’s age. BSARV has a common normal range for all age groups with the 10th percentile of 45 and the 90th percentile of 85 mL/m2. 80% of all kidneys do not exceed the volume of their counterparts by more than 20%. BSARV alleviates the correct evaluation of a child’s renal volume regardless of age and reveals pathological influences by the simple observation that a kidney deviates from a former percentile or z-value. This is especially valuable in the followup of kidneys with chronic diseases.